Measurement of two-neutrino double electron capture half-life of 124Xe with PandaX-4T - The PandaX-4T collaboration; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Journal of High Energy Physics)
Abstract Detailed studies of two-neutrino double electron capture (2νDEC) is a crucial step towards searching for the neutrinoless mode to explore the Majorana nature of neutrinos. We have measured precisely the half-life of the 2νDEC process in 124Xe, utilizing a total exposure of 1.73 tonne year from the commissioning run and the first science run of the PandaX-4T experiment. A time-dependent background model in the O $$ \mathcal{O} $$ (10 keV) energy is constructed for the first time in PandaX-4T data. With an unbinned maximum likelihood fit, we determine the half-life of the 2νDEC process to be (1.03 ± 0.15stat ± 0.08sys) × 1022 yr. Furthermore, we have evaluated the capture fraction for both electrons captured from the K shell (KK) to be (65 ± 5)%, which aligns with the 124Xe nuclear model calculations within 1.8 σ.